Congruence in European and Asian perception of Vietnamese facial attractiveness, averageness, symmetry and sexual dimorphism - Ondřej Pavlovič; Vojtěch Fiala; Karel Kleisner (Scientific Reports, 2023)
Abstract Attractiveness is a proposed universal cue to overall biological quality. Nonetheless, local raters and raters of the same ethnicity may be more accurate in assessing the cues for attractiveness than distant and unfamiliar raters. Shared ethnicity and shared environment may both affect rating accuracy: our aim was to compare their relative influence. Therefore, we photographed young Vietnamese participants (N = 93, 33 women) from Hanoi, Vietnam. The photographs were rated by Czechs, Asian Vietnamese, and Czech Vietnamese (raters of Vietnamese origin who lived in Czechia for all or most of their life). Using geometric morphometrics, we measured facial shape cues to biological quality: averageness, asymmetry, and sexual dimorphism. We expected that Vietnamese raters residing in Czechia and Vietnam would agree on perceived attractiveness and use shape-related facial cues to biological quality better than Czech European raters, who are less familiar with East Asians. Surprisingly, mixed-effect models and post hoc comparisons identified no major cross-group differences in attributed attractiveness and path analyses revealed that the three groups based their rating on shape-related characteristics in a similar way. However, despite the considerable cross-cultural agreement regarding perceived attractiveness, Czech European raters associated attractiveness with facial shape averageness significantly more than Vietnamese raters.